2015
DOI: 10.3329/jbsp.v9i2.22801
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Aging on Short Term Heart Rate Variability

Abstract: Background: Heart rate variability has been considered as an indicator of autonomic nerve function status. Few works have been done to assess the heart rate variability in normal healthy subjects in different countries. Objectives: To assess the cardiac autonomic nerve function status in healthy Bangladeshi population of different age groups by analyzing time domain measures of Heart Rate Variability. Methods: This cross sectional study was conducted in the Department of Physiology, Dhaka Medical College, Dhak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 20 publications
1
3
0
Order By: Relevance
“…Besides HRV being used to detect drowsiness, in this work it will be investigated, whether factors affecting and altering HRV among humans are also reflected in the development of drowsiness detection models and the resulting detection accuracy will also be investigated. Age, in particular, has a strong effect on HRV, which has already been investigated and confirmed in numerous studies, both in the context of long-term (Umetani et al, 1998) and in short-term measurements (Akhter et al, 2015;Voss et al, 2015;Nunan and Brodie, 2010), which are part of this work. In general, from the results in previous work, it can be said that a lower HRV indicates higher biological age (older) (O'Brien et al, 1986).…”
Section: Feasibility Of Smart Wearables 1 1 Introductionsupporting
confidence: 76%
“…Besides HRV being used to detect drowsiness, in this work it will be investigated, whether factors affecting and altering HRV among humans are also reflected in the development of drowsiness detection models and the resulting detection accuracy will also be investigated. Age, in particular, has a strong effect on HRV, which has already been investigated and confirmed in numerous studies, both in the context of long-term (Umetani et al, 1998) and in short-term measurements (Akhter et al, 2015;Voss et al, 2015;Nunan and Brodie, 2010), which are part of this work. In general, from the results in previous work, it can be said that a lower HRV indicates higher biological age (older) (O'Brien et al, 1986).…”
Section: Feasibility Of Smart Wearables 1 1 Introductionsupporting
confidence: 76%
“…In the 24-hour Holter recordings, Reardon et al [18] proved that aging reduced the global HRV measure and concluded that the process may reflect a reduced responsiveness of autonomic activity to various stimuli with age. In another study performed by Akhter et al [19], cardiac autonomic impairment with the advancement of age was demonstrated, and the detailed HRV analysis demonstrated a decreased parasympathetic function. Those findings were confirmed by Shankar and Veeraiah [20] who demonstrated a parasympathetic dysfunction in the elderly, using classical Ewing's clinical autonomic tests (deep breathing, Valsalva maneuver, standing orthostatic response).…”
Section: Discussionmentioning
confidence: 89%
“…9,11,[15][16][17] Similarobservations were reported by the researchers in our country. [18][19][20][21][22] Different timedomain components of HRV has been used as marker of cardiac autonomic activity. 13 The task force guideline for HRV analysis have demonstrated the interpretation of these parameters to understand the status, behaviour and the balance between sympathetic and parasympathetic due to their continuous interaction.…”
Section: Discussionmentioning
confidence: 99%